MIELOMA MULTIPEL NONSECRETORY (Nonsecretory Multiple Myeloma) - Maimun Zulhaidah Arthamin; Nyi R. Wahidah; Boy A. Sihite (Indonesian Association of Clinical Pathologist and Medical laboratory, 2015)
The incidence of non-secretory multiple myeloma ranged between 1−5% cases of plasma cell dyscrasia (PCD). In the developedcountries like in Europe, cases of MM ranged from 4.5 up to 6.0/100.000 population/year with a median age at diagnosis between63 and 70 years. A very rare disease with difficulties in diagnosis in the clinical practice is the main reason for reporting this case.A nonsecretory MM (MMNS) case was reported in a 36–year-old male with multiple osteolytic lesions and bone pain; whereas renalinsufficiency as well as anemia was not found. The protein electrophoresis result showed a presence of hypoglobulinemia. On bone marrowaspiration (BMA) there was an infiltration of about 40% of plasma cells. Nonsecretory was due to a disruption of immunoglobulinsecretion, so M protein was not found in immuno-fixation electrophoresis. Epidemiological data showed that the incidence of MM inyoung age is very low. The diagnosis of MMNS is established when a plasmocyte neoplasm is not accompanied by renal insufficiency,hypercalcemia and decreased levels of normal immunoglobulin.